(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
إنّ الهدف الرّئيس للبحث هو التّعرّف على العوامل المؤثرة في القدرة التنافسية للمدقق الخارجي في بيئة الأعمال السّوريّة. لتحقيق هدف البحث تم إجراء دراسة ميدانيّة على مدققي حسابات الشّركات المساهمة السّوريّة عن طريق استخدام استبانة لجمع البيانات من أفراد مجتمع البحث المكوّن من مدققي الحسابات المعتمدين من قبل وزارة المالية، والمسموح لهم بتدقيق حسابات الشركات المساهمة تم توزيعها على (275) مدقق حسابات من أصل (493) مدقق حسابات، استُردّ منها (117) استبانة، وتمّ تفريغ (115) استبانة كونها صالحة للتحليل. توصّل الباحث إلى أنّ العوامل المؤثرة في القدرة التنافسية للمدقق الخارجي السوري هي: مستوى جودة الأداء المهني للتدقيق، ودرجة الالتزام بالمعايير الدوليّة للتدقيق، وعملية تحديد أتعاب التدقيق، وحجم مكتب التدقيق، والخدمات الأخرى التي يقدمها المدقق الخارجي، ووجود النفوذ الاجتماعي للشركاء في مكتب التدقيق، ومستوى تخصص مكتب التدقيق في النشاط أو الصناعة، وجود لجان تدقيق عند العملاء. The main objective of this research is to identify the Factors Affecting Competitive Ability of the Syrian External Auditor. To achieve the objective of this research, a field study was conducted by using a questionnaire to collect data from the population of the study which is composed of auditors accredited by the Finance Ministry, and authorized to audit shareholding companies. The questionnaire was distributed to 275 out of 493 auditors. 117 copies were returned, and 115 of them were suitable for analysis. The researcher concluded that the Factors Affecting Competitive Ability of the Syrian External Auditor, is the level of audit quality, the preexistent degree of International Accounting Standards, operation of auditors fees definition, size firm, and non audit services, and social influence of accounting firm, industrialist specialize of auditor, and the exist of audit committee at the client.